Role of Microbiome in Modulating Immune Responses in Cancer - Mukulika Bose; Pinku Mukherjee (Hindawi Limited, 2019)
The complex interactions between genes and the environment play important roles in disease susceptibility and progression. One of the chronic diseases that is affected by this gene-environment interplay is cancer. However, our knowledge about these environmental factors remains limited. The microorganisms that inhabit our bodies have recently been acknowledged to play a crucial role as an environmental factor, to which we are constantly exposed. Studies have revealed significant differences in the relative abundance of certain microbes in cancer cases compared with controls. It has been reported that changes in the composition of normal gut microbiota can increase/decrease cancer susceptibility and progression by diverse mechanisms including, but not limited to, inflammation-a well-known hallmark of carcinogenesis. The microbiota can also affect the response to various treatments including immunotherapy. The microbiome-immune-cancer axis will continue to provide insight into the basic mechanisms of carcinogenesis. In this review, we provide a brief understanding of the mechanisms by which microbiota affects cancer development, progression, and treatment.